Drama is for Life! Recreational Drama Activities for the Elderly in the UK - Sextou, Persephone; Smith, Cory (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Applied Theatre is an inclusive term used to host a variety of powerful, community-based participatory processes and educational practices. Historically, Applied Theatre practices include Theatre-in-Education (TiE), Theatre-in-Health Education (THE), Theatre for Development (TfD), prison theatre, community theatre, theatre for conflict resolution/reconciliation, reminiscence theatre with elderly people, theatre in museums, galleries and heritage centres, theatre at historic sites, and more recently, theatre in hospitals. In this paper we are positioning the application of recreational dramatic activities with older adults (55+) under Applied Theatre and we are exploring the benefits they offer to the participants. We are concerned that their health and wellbeing in western societies is not prioritized and it is clear that loneliness in particular is a current and ongoing issue. We will present research results from a drama dissertation study that took place in a community hall in the South East England where drama is placed at the core of their practice with old populations. Data was collected by a mixed method (semi-structured interviews and semi-immersive observations) and was critically discussed amongst the authors to conclude that attending recreational drama classes brings a certain degree of happiness, social belonging and improvement of interaction with others to old people’s lives.